Religious Tourism Demand and Country Prosperity: An Empirical Study of Saudi Arabia - Alanzi, Eman Mealith (The international journal of religious tourism and pilgrimage, 2023)
This study examines the impact of destination prosperity level on religious tourism flows to Saudi Arabia. The model was empirically tested for a panel of 21 countries from 2000 to 2019. Dynamic panel gravity models were estimated using the Generalised Method of Moments (GMM) difference approach. The study found that the human rights index and prosperity index, word of mouth, Saudi Arabian income, origin country income and investment in tourism at the destination all had a positive and significant impact on religious tourism demand. In contrast, the cost of travel and cost of living at the destination, political risk, visa restrictions, and the relative temperature had an inverse and significant impact. The estimated coefficients suggest that Saudi Arabia should invest in high-quality services to make religious visits a more pleasant and memorable experience. The paper’s originality is in using new non-economic factors such as prosperity and human rights as well as economic factors in estimating tourism demand for religious purposes.